Hydraulic Design of Geosynthetic and Granular Liquid Collection Layers Comprising Two Different Slopes. Issue 4 (1st January 2000) - Beech, J.F.; Zornberg, J.G.; Giroud, J.P.
Abstract : Liquid collection layers used in landfills often comprise two sections with different slopes. Typically, one of the slopes is much steeper than the other one. The steeper slope is generally the downstream slope in a landfill cover and the upstream slope in a leachate collection layer. The liquid collection material is generally a geosynthetic (such as a geonet) on the steep slope and is either a geosynthetic or a granular material (such as sand or gravel) on the other slope. Design methods are available for the case where there is a drain that promptly removes the liquid at the toe of each of the two sections. This paper provides a method to design the liquid collection layer for the case where there is no drain at the connection between the two sections, i.e. when the only drain is at the toe of the downstream section. The method consists of analytical expressions for calculating the maximum thickness of liquid under steady-state conditions in each of the two sections of the liquid collection layer. Design examples are presented and practical guidance is provided for the use of a transition zone between the two sections when needed.